Vochysia peruviana (Vochysiaceae), a new species from Flooded Forests, Madre de Dios, Peru - Huamantupa-Chuquimaco, Isau (Phytotaxa, 2017)
Vochysia peruviana is described and illustrated as a new species. It occurs in the Madre de Dios region of southern Peru, where is associated to flooded forests in the Amazonian lowlands. This species is placed in Vochysia section Ciliantha subsection Ferrugineae. It is compared with the most closely related species, V. ferruginea and V. floribunda.